Nueva República, nuevo horizonte, nuevo porvenir: las migraciones colombianas hacia Chile, 1990-2016 (2018)
As a result of the great economic growth in Latin America throughout the first decade of the twenty-first century, the development of migrations towards certain destinies inside the region experienced a significant upturn comparable with the massive migration waves in the nineteenth century. Chile stands out due to its growing immigration boom, as the destiny of numerous people migrating from other South American countries, including Colombia. Thus, the main purpose of this paper is to understand the nature and development of the phenomenon of Colombian migration to Chile, as a matter of high importance in the main immigration situation in the last 15 years. It is our hope that the reader will be able to understand the real dimension of this phenomenon as an agent that directly affects the new transformations of Colombian migration abroad.